Designing the automatical system making course reports - Hồ Quang Khải; Võ Thu Phụng (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
The automatic course reporting system automates the implementation of course reports at the Faculty of Information Technology, Ho Chi Minh City Open University. This system helps save time and achieve accurate and diverse results. Input data for the system are compiled, then filtered, processed, and standardized to suit the implementation of the course reports. The system software has been tested and has created course reports with good results and more information than the University’s requirements. This system supports the Faculty Board and lecturers in monitoring the teaching situation, ensuring the achievement of the expected training outcomes, and gradually enhancing the quality of the course output. Lecturers have specific data on training results to improve their teaching. The Faculty Board has particular information on modifying training administration and assigning lecturers based on their abilities and expertise.